ChemInform Abstract: Research Advances in Deriving Renewable Energy from Biomass in Wastewater Treatment Plants. Issue 31 (14th July 2016) - Zhang, Yuan‐kai; Liu, Xiu‐hong; Liu, Xiao‐wei; Zha, Yi‐fei; Xu, Xiang‐long; Ren, Zheng‐guang; Jiang, Hang‐cheng; Wang, Hong‐chen
Abstract: Review: 161 refs.